AJENG DALAM KONTEKS TRADISI PERKAWIN-AN KHAS KARAWANG - Ocid, Dandi (Paraguna, 2023)
Etymologically, Ajeng comes from the word "pangajeng-ngajeng" which means honor. Ajeng art is a folk art that has been developed from generation to generation from previous heirs which functions as a medium for welcoming ceremonies both sacred and entertainment. In the context of Ajeng's continued existence, the development process cannot be separated from the participation of various parties. Related institutions through activities such as; seminars, training, documenting and making teaching material books for local content in schools are significant efforts in the preservation of traditional arts, especially Ajeng in the context of Karawang.